Classification and Differential Diagnosis of Diabetic Nephropathy - Chenyang Qi; Xing Mao; Zhigang Zhang; Huijuan Wu (Journal of Diabetes Research)
Diabetic nephropathy (DN) is a major cause of end-stage renal disease throughout the world in both developed and developing countries. This review briefly introduces the characteristic pathological changes of DN and Tervaert pathological classification, which divides DN into four classifications according to glomerular lesions, along with a separate scoring system for tubular, interstitial, and vascular lesions. Given the heterogeneity of the renal lesions and the complex mechanism underlying diabetic nephropathy, Tervaert classification has both significance and controversies in the guidance of diagnosis and prognosis. Applications and evaluations using Tervaert classification and indications for renal biopsy are summarized in this review according to recent studies. Meanwhile, differential diagnosis with another nodular glomerulopathy and the situation that a typical DN superimposed with a nondiabetic renal disease (NDRD) are discussed and concluded in this review.